Effect of electrokinetic treatment time on energy consumption and salt ions removal from clayey soils - Hussain, Abdul Ahad; Kamran, Kashif; Hina, Maryam; Ishaq, Mubashera; Naz, Muhammad Y; Bashir, Shahid; Sarwar, Nadeem; Quazi, Moinuddin Mohammed (Institute of Physics, 2023)
Electrokinetics effectively removes contaminants, but its field-scale applications are limited mainly due to its high energy cost. In previous studies, the energy consumption was determined either by changing the soil’s specimens initial salt concentration while keeping the treatment time fixed or by changing the treatment time and keeping the same initial salt concentrations for all the specimens. Since both the initial salt concentration and treatment time are important parameters in determining reclamation cost, therefore, in this study, the soil specimens intentionally contaminated with different concentrations of sodium chloride (NaCl), i.e., varying from 3.7 to 15.5 g kg−1, were exposed to a constant DC electric field of 1 V cm−1 for different time durations, i.e., varying from 6 to 72 h. The results show that electroosmotic flow (EOF) was directed from the anode to the cathode and higher for specimens contaminated with relatively low salt concentration, i.e., up to 7.6 g kg−1. Therefore, for these specimens, due to the combined effect of electroosmosis and electromigration, the removal of Na+ was higher than the Cl−. However, for the specimen contaminated with a higher salt concentration, i.e., 15.5 g kg−1, the Cl− removal exceeded Na+ due to the marginalization of EOF. Regardless of initial salt concentration, the electroosmotic flow and salt ions removal rates decreased with increasing treatment time, which might be attributed to the development of acidic and alkaline environments in soil. The collision of acidic and alkaline fronts resulted in a large potential gradient in a narrow soil region of pH jump, diminishing it everywhere else. This nonlinearity in the electric potential distribution in soil reduced the EOF and electromigration of salt ions.